RANCANG BANGUN SISTEM INFORMASI ASET MENGGUNAKAN UNIFIED MODELLING LANGUAGE - Devi Astri Nawangnugraeni; M. Zakki Abdillah; Akrim Teguh Suseno (Jurnal Teknologi Informasi Mura, 2021)
Assets means of supporting business processes in an agency, one of which is building assets. The asset requires organized systematically and structured management. One of the alternatives in asset management is by using a web-based information system. The research describes the design of asset management information systems owned by PCNU Pekalongan. This web-based asset information system designed using the Unified Modeling Language (UML). This system development method uses Waterfall and tested with blackbox testing. Based on the results of blackbox testing, it can be concluded that asset information system has good functionality and has no errors. With this development, it can increase the effectiveness of asset management at PCNU Pekalongan. Keywords— Information System, Web, Asset, Unified Modelling Language